2016
DOI: 10.3171/2015.10.spine15455
|View full text |Cite
|
Sign up to set email alerts
|

How to predict return to work after lumbar discectomy: answers from the NeuroPoint-SD registry

Abstract: OBJECTIVE To date, the factors that predict whether a patient returns to work after lumbar discectomy are poorly understood. Information on postoperative work status is important in analyzing the cost-effectiveness of the procedure. METHODS An observational prospective cohort study was completed at 13 academic and community sites (NeuroPoint–Spinal Disorders [NeuroPoint-SD] registry). Patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
4
17
2
Order By: Relevance
“…In a holistic approach, we also assessed function through the patients’ occupation status, symptom they would most value treatment for, and NHS service use post-discharge. In patients of working age, we found 71% were able to return to full employment, roughly matching the data from previous studies regarding spinal surgery which found 67% patients were able to return to work over a 3-month to 5-year follow-up [25].…”
Section: Discussionsupporting
confidence: 89%
“…In a holistic approach, we also assessed function through the patients’ occupation status, symptom they would most value treatment for, and NHS service use post-discharge. In patients of working age, we found 71% were able to return to full employment, roughly matching the data from previous studies regarding spinal surgery which found 67% patients were able to return to work over a 3-month to 5-year follow-up [25].…”
Section: Discussionsupporting
confidence: 89%
“…Older age (OR 0.92; 95% CI 0.85 to 0.99) predicted reduced RTW at 3 months 28. Passive pain coping (OR 1.08, SE 0.04, estimated 95% CI 1.00 to 1.1726 and higher physical work load (OR 1.19, SE 0.06, estimated 95% CI 1.06 to 1.34)26 predicted reduced RTW at 6 months.…”
Section: Resultsmentioning
confidence: 97%
“…The number of participants varied from 46 to 394 per cohort, mean age ranged from 35 to 46 years, 28%–78% were male and all analyses included working populations. Two cohorts measured short-term follow-up at 328 and 6 months 26. Long-term outcomes ranged from 2,22 25 3,27 423 to 10 years24 follow-up, with the majority measured between 2 and 4 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,12,24 This may be attributed to the fact that these represent a more driven subset of patients who have better social support, work satisfaction, healthier psychological state, availability of modified duty, optimum physical demand at work, and employer-employee relations including the availability of litigation issues. 4,5,12,26,31,34,40 Together, these factors may contribute to these patients having superior outcomes after spine surgery.…”
Section: Discussionmentioning
confidence: 99%